Case Report: Long-term remission of malignant pleural and peritoneal effusion in a case of advanced lung adenocarcinoma treated with combined crizotinib and anlotinib therapy - Tian, Jin; Long, Lin; Zang, Jianhua; Liu, Peng; Zhao, Lili; Zhang, Hongtao; Xiao, Jun (Frontiers in Oncology, 2023)
Malignant pleural and peritoneal effusion are common clinical manifestations in advanced malignant tumors, associated with a poor prognosis. This article presents a case of advanced lung adenocarcinoma with ROS1 rearrangement, characterized by persistent malignant pleural and peritoneal effusion. The patient received combined therapy of Crizotinib and Anlotinib, resulting in a significant reduction and even disappearance of the malignant effusion. Exploratory use of this treatment approach improved the patient’s quality of life and holds potential for extending overall survival. However, given the single case report nature, the efficacy of this regimen in treating advanced ROS1-rearranged lung adenocarcinoma should be considered as a supplementary strategy, warranting further validation through multicenter clinical data.